2017
DOI: 10.1002/cbin.10896
|View full text |Cite
|
Sign up to set email alerts
|

miR‐23b‐3p and miR‐125b‐5p downregulate apo(a) expression by targeting Ets1 in HepG2 cells

Abstract: High concentrations of plasma lipoprotein(a) [Lp(a)] have been inferred to be an independent risk factor for cardiovascular and cerebrovascular diseases, such as coronary artery diseases, restenosis, and stroke. Apolipoprotein(a) [apo(a)] is one of the most important components of Lp(a) and contributes greatly to the increased concentration of plasma Lp(a). As a critical positive transacting factor of apo(a) gene, Ets1 has been proven as a target gene of several miRNAs, such as miR-193b, miR-125b-5p, miR-200b,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Fourteen miRNAs were identified as atherosclerosis related in both models, including three previously reported miR-NAs that contribute to atherogenesis in different mechanisms of action. For example, miR-23b-3p has been shown to inhibit the synthesis of apo(a), one of the most important components of Lp(a), by targeting Ets1, increasing the risk of cardiovascular diseases (39). miR-30a-5p is correlated with calcification extension by targeting RUNX family transcription factor 2, and significantly upregulated in the arterial calcified culprit plaques of patients with acute coronary syndromes (40).…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen miRNAs were identified as atherosclerosis related in both models, including three previously reported miR-NAs that contribute to atherogenesis in different mechanisms of action. For example, miR-23b-3p has been shown to inhibit the synthesis of apo(a), one of the most important components of Lp(a), by targeting Ets1, increasing the risk of cardiovascular diseases (39). miR-30a-5p is correlated with calcification extension by targeting RUNX family transcription factor 2, and significantly upregulated in the arterial calcified culprit plaques of patients with acute coronary syndromes (40).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been speculated that miR-23b-3p is also involved in fat metabolism, the conclusions are inconsistent. A study found that in HepG2 cells, miR-23b-3p inhibits the synthesis of ApoA protein, which is a risk factor for thrombotic diseases (Zeng et al, 2018), whereas another study reported that SIRT1, an enzyme that prevents lipid accumulation, was repressed by hsa-miR-23b-3p in hepatocytes (Borji et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of miR‐125a‐5p is increased in hyperlipidemic (Simionescu, Niculescu, Sanda, Margina, & Sima, ). A previous study revealed that downregulation of apo(a) expression by miR‐125b‐5p by targeting Ets1 in HepG2 cells is related to As (J. F. Zeng, Zeng, et al, ). Nevertheless, whether miR‐125a‐5p is involved in VEC death upon oxLDL exposure and its relation to TET2 downregulation remain to be clarified.…”
Section: Introductionmentioning
confidence: 99%